Unraveling the Association between Poverty and Crime Rates in Urban Areas: Causes, Consequences, And Policy Implications - Mubarik Ali; Asfand Yar; Norina Jabeen; Muhammad Bilal (Indus Journal of Social Sciences, 2023)
Objectives: This study aimed to investigate the relationship between poverty and crime rates in urban areas of Sindh, Pakistan. Methods: A quantitative approach was employed, utilizing a cross-sectional design and data from 150 participants. Crime data were collected from local law enforcement agencies, while poverty data were obtained from government sources and census records. Results: Descriptive statistics revealed that the average crime rate in the urban areas of Sindh was 28.10, with a standard deviation of 3.14. The average income level was 17,000 (Rs.), with a standard deviation of 3,500, while the average unemployment rate was 75.87%, with a standard deviation of 10.78. The average education level was 67.98%, with a standard deviation of 10.32. Statistical analyses, including ANOVA tests, indicated a significant association between poverty indicators (income levels, unemployment rates, and education levels) and crime rates (p < 0.05). Conclusion: The findings highlighted that higher poverty levels, higher unemployment rates, and lower education levels were linked to higher crime rates in urban areas of Sindh. These findings emphasized the importance of implementing comprehensive interventions that address poverty as a key factor in crime prevention and reduction strategies in urban areas.